Isolation and Culture of Microglia. (10th November 2018) - Bohlen, Christopher J.; Bennett, F. Chris; Bennett, Mariko L.
Abstract: Microglia represent 5‐10% of cells in the central nervous system and contribute to the development, homeostasis, injury, and repair of neural tissues. As the tissue‐resident macrophages of the central nervous system, microglia execute core innate immune functions such as detection of pathogens/damage, cytokine secretion, and phagocytosis. However, additional properties that are specific to microglia and their neural environment are beginning to be appreciated. This article describes approaches for purification of microglia by fluorescence‐activated cell sorting using microglia‐specific surface markers and for enrichment of microglia by magnetic sorting and immunopanning. Detailed information about culturing primary microglia at various developmental stages is also provided. Throughout, we focus on special considerations for handling microglia and compare the relative strengths or disadvantages of different protocols. © 2018 by John Wiley & Sons, Inc.